Investigating the Interaction between Spatial Perception and Working Memory in the Human Medial Temporal Lobe - Lee, Andy C. H. (2010)
There has been considerable debate surrounding the functions of the medial temporal lobe (MTL). Although this region has been traditionally thought to subserve long-term declarative memory only, recent evidence suggests a role in short-term working memory and even higher-order perception. To investigate this issue, functional neuroimaging was used to investigate the involvement of the MTL in spatial scene perception and working memory. Healthy participants were scanned during a working memory task incorporating two factors of working memory (high vs. low demand) and spatial processing (complex vs. simple). It was found that an increase in spatial processing demand produced significantly greater activity in the posterior hippocampus and parahippocampal cortex irrespective of whether working memory demand was high or low. In contrast, there was no region within the MTL that increased significantly in activity during both the complex and simple spatial processing conditions when working memory demand was increased. There was, however, a significant interaction effect between spatial processing and working memory in the right posterior hippocampus and parahippocampal cortex bilaterally: an increase in working memory demand produced a significant increase in activity in these areas during the complex, but not simple, spatial processing conditions. These findings suggest while there may be a role for the MTL in both stimulus processing and working memory, increasing the latter does not necessarily increase posterior MTL involvement. We suggest that these structures may play a critical role in processing complex spatial representations, which, in turn, may form the basis of short- and long-term mnemonic processes.